A Computed Tomography Radiomics-Based Prediction Model on Interstitial Lung Disease in Anti-MDA5-Positive Dermatomyositis - Xu, Wenwen; Wu, Wanlong; Zheng, Yu; Chen, Zhiwei; Tao, Xinwei; Zhang, Danting; Zhao, Jiangfeng; Wang, Kaiwen; Guo, Bingpeng; Luo, Qun; Han, Qian; Zhou, Yan; et al. (Frontiers in Medicine, 2021)
Objectives Anti-melanoma differentiation-associated gene 5-positive dermatomyositis-associated interstitial lung disease (MDA5+ DM-ILD) is a life-threatening disease. The current study aimed to quantitatively assess the pulmonary HRCT images of MDA5+ DM-ILD by applying the radiomics approach and establish a multidimensional risk prediction model for the 6-month mortality. Methods This retrospective study was conducted in 228 patients from two centers, including a derivation cohort and a longitudinal internal validation cohort in Renji Hospital; as well as an external validation cohort in Guangzhou. The derivation cohort was randomly divided into training and testing sets. The primary outcome was 6-month all-cause mortality since the time of admission. Baseline pulmonary HRCT images were quantitatively analyzed by radiomics approach and a radiomic score (Rad-score) was generated. Clinical predictors selected by univariable Cox regression were further incorporated with the Rad-score, to enhance the prediction performance of the final model (Rad-score plus model). In parallel, an idiopathy pulmonary fibrosis (IPF)-based visual CT score and ILD-GAP score were calculated as comparators. Results The Rad-score was significantly associated with the 6-month mortality, outperformed the traditional visual score and ILD-GAP score. The Rad-score plus model was successfully developed to predict the 6-month mortality, with C-index values of 0.88 (95% confidence interval [CI], 0.79–0.96) in the training set (n = 121), 0.88 (95%CI, 0.71–1.0) in the testing set (n = 31), 0.83 (95%CI, 0.68–0.98) in the internal validation cohort (n = 44), and 0.84 (95%CI, 0.64–1.0) in the external validation cohort (n = 32). Conclusions The radiomic feature was an independent and reliable prognostic predictor for MDA5+ DM-ILD.